HABIT OF CONGREGATIONAL PRAYER IN IMPROVING STUDENTS' MORALS - Luklu Urrohmah; Rahmad Dede Suderman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
A good habit is very necessary to build a religious character. Good habits can be done through additional program activities in schools. The habituation of the program carried out is expected to be a provision for students in the next period. The objectives of this study are 1) Implementation of the habit of praying Dzuhur in congregation in improving the morals of students in schools 2) Supporting factors for the habit of praying Dzuhur in congregation in improving the morals of students in schools. 3) Strategy for the habit of praying Dzuhur in congregation in improving the morals of students at SMAS Islam Kebumen. This research is a field research. The nature of this research is descriptive research, namely a form of research that is shown to explain existing phenomena. Conclusion 1) The habit of praying Dzuhur in congregation in improving the morals of students. 2) Supporting factors for the habit of praying Dzuhur in congregation in improving the morals of students 3). Strategy for the habit of praying Dzuhur in congregation in improving the morals of students